Studying the effect on the properties of fume silica percent formulated grease - M. Fakhrur Azhar, Tukiman (2009)
Vegetable oil has significant potential as a base fluid and substitute for mineral oil for grease formulation. Vegetable oils are promising candidates as base fluid for eco-friendly lubricants because of their excellent lubricity, biodegradability, viscosity-temperature characteristic and low volatility. This paper presents the effective and ability of grease by using natural material. Performance characteristics of greases used for industrial and automotive application are largely depending on the hardness. Grease hardness was determined using standard test methods. Results indicate that the fume silica percent in formulated grease are directly proportional to the viscosity and drop point. There is no drop point at 310°C occur more than 10%wt of fume silica. Also, the grease didn’t show negative effect on the metal surface. Therefore, developed greases can be a good substitute for mineral oil-based greases in industrial, agriculture, forestry and marine application.